The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1063/1.3664112
|View full text |Cite|
|
Sign up to set email alerts
|

Even-odd symmetry and the conversion efficiency of ideal and practical graphene transistor frequency multipliers

Abstract: Erratum: "Even-odd symmetry and the conversion efficiency of ideal and practical graphene transistor frequency multipliers" [Appl. Phys. Lett. 99, 223512 (2011)] Appl. Phys. Lett. 102, 179902 (2013); 10.1063/1.4804263 A computational study of high-frequency behavior of graphene field-effect transistors A high-performance top-gate graphene field-effect transistor based frequency doubler

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 17 publications
(22 reference statements)
1
8
0
Order By: Relevance
“…Aggressive gate oxide scaling is required to enhance the conversion efficiency, together with the suppression of non-ideal factors, such as high contact resistance and impurity concentration. 23 The high conversion gain in this work supports that the proposed inverted integration process is suitable for GFETs fabrication. Fig.…”
Section: Graphene Frequency Multipliersupporting
confidence: 72%
“…Aggressive gate oxide scaling is required to enhance the conversion efficiency, together with the suppression of non-ideal factors, such as high contact resistance and impurity concentration. 23 The high conversion gain in this work supports that the proposed inverted integration process is suitable for GFETs fabrication. Fig.…”
Section: Graphene Frequency Multipliersupporting
confidence: 72%
“…Moreover, the previously reported works have shown that the microscopic mechanisms that cause such effects in graphene are very different and strongly enhanced when compared with those observed in conventional semiconductors [2,14]. High-efficiency second-and third-harmonic generation effects have been achieved in monolayer graphene-based transistors, from relatively low frequencies up to the millimeter-wave frequency band [15][16][17], and they have also been experimentally observed in few-layer graphene sheets [6,8,11,13].…”
Section: Introductionmentioning
confidence: 97%
“…This capability was experimentally demonstrated through a wide variety of experiments covering from the low microwave region to the optical domain, describing the generation of second- [19]- [22] and third-order [23]- [25] harmonic components, and performing frequency mixing [26]- [28]. Furthermore, several graphene-based transistors [29]- [32] have also been reported.…”
Section: Introductionmentioning
confidence: 94%